Caracterización agromorfológica de 20 accesiones de arveja (Pisum sativum) del banco activo de semillas de la Universidad Técnica de Cotopaxi en la parroquia de Constantino Fernández perteneciente al cantón Ambato. - Proaño Altamirano, Edison Leonidas (2021)
The mission of the Germplasm Characterization Area is to promote the knowledge and valuation of plant genetic resources through scientific research, the conservation of biological diversity, environmental education and recreation, to contribute effectively to the conservation and sustainable use of the environment. The present research characterized 20 peas ecotypes, in the parish of Constantino Fernandez in the canton of Ambato, province of Tungurahua. The objectives were focused on determining the variability that exists among all ecotypes, We also identified the best accessions that have been adapted to the area and of which they have been able to give their best yields to later be taken to the active bank of Andean Seeds and Grains of the Technical University of Cotopaxi, to continue researching. In the present research 20 ecotypes were collected in the provinces of Tungurahua and Cotopaxi, a random seeding was carried out taking into account the density seeding of the crop. Where agronomic and morphological characteristics were evaluated and the best ecotypes that were developed under the edaphoclimatic conditions of the area were selected. From the results obtained in the management of the trial and after the tabulation of data through the statistical interaction it was determined that the access "5" was the best germ with 85.4% of germinated plants, in the description of height, the access "12" protruded with an average height of 71.4cm. , in the same way the accession "12" arrived first to the flowering at 42 days and the ecotypes"1 4 and 12" managed to reach more than three flowers per knot which at the time obtained more number of pods.Genetic diversity was determined among the accessions studied as they showed morphological and agronomic differences. It is recommended to evaluate the adaptability of the most outstanding accessions to arid zones since many accessions have favorable characteristics in order to find a variety that is resistant.